(untitled) (Konturen, 2013)
The Berlin Wall is – in spite of its obvious function and its supposedly simple form (Gestalt) – an object that must be read carefully. Countless attempts have been made to analyze the significance of the Berlin Wall. The present analysis does not make use of statistics, mass media representations, or historical moralities in its attempt to arrive at a new understanding of the Wall. Instead, the focus is on the Wall as a complex architectural form and its function for a second German national literature after 1961.